The Ideological Drivers Behind the Support for the Use of Direct Democracy among Voters and Parties of Benelux Countries - Paulis, Emilien; Rangoni, Sacha (Politics of the Low Countries, 2025)
The use of referendums has gained popularity among both voters and parties. Yet, despite the diffusion of such direct forms of democracy during the last decades in Europe, referendums remain not a very common policy instrument in Benelux countries (Belgium, the Netherlands and Luxembourg). We establish that this trend could be explained by a large consensus among mainstream (especially right) parties and voters against the use of direct democracy. Moreover, we confirmed the well-established demarcation with radical ideologies, which convey overall more support and congruence on the use of referendums than the mainstream. Additionally, and probably reflecting this new line of cleavage, we show that support for referendums among the voters relate to left-wing economic position, but also with culturally right-wing view. Overall, this article questions the relevance of the traditional left-right divide to explain support for direct democracy, as well as the capacity for (some) parties to align with their voters in terms of democratic demands.